The waterfowl of the Fraser Delta, British Columbia - Leach, Barry A (Wildfowl, 1972)
The Fraser River Delta, British Columbia, has extensive waterfowl habitat with both estuarine and freshwater marshes. Drainage and reclamation has significantly reduced these areas but sufficient remains to support substantial numbers of wintering waterfowl of a wide variety of species. The Delta is also of importance to migrant waterfowl, while small numbers breed there. Industrial and urban growth and increased hunting pressure are having detrimental effects on the wintering waterfowl population and it is vital that the various habitats are conserved, and sanctuaries provided to reduce the disturbance from shooting. The breeding population would benefit from the provision of nesting boxes and protection from predators. Habitat management is seen as the answer to the various threats.